Edukasi Kepada Masyarakat Pemanfaatan Sari Buah Bit Menjadi Sabun Mandi Cair yang Berkhasiat sebagai Pelembab Kulit - Devina Chandra; Natanael Priltius; Betharina Br Tarigan (Jurnal Pengabdian Bidang Kesehatan, 2024)
Liquid bath soap is a liquid preparation used to clean the skin, made from soap base ingredients with added surfactants, foam stabilizers and fragrances, which is used when bathing without causing irritation to the skin. Liquid bath soap is made by saponifying oil and fat with KOH. This community service is carried out to provide education to the public about beetroot juice as a skin moisturizer. This method of community service is by providing education to the public by presenting material about beetroot juice which treats skin moisture and introducing natural ways to use beetroot juice. The results of the activities of implementing the community service program are in the form of educating the public about the benefits of beetroot juice, namely as a skin moisturizer. Conclusion: Community service in managing beetroot juice as a skin moisturizer meets quantity and quality.